Morphological Characteristics and Situational Precision of U15 and U16 Elite Male Players from Al-Ahli Handball Club (Bahrein) - Boris Banjevic; Boris Zarkovic; Borko Katanic; Blazo Jabucanin; Stevo Popovic; Bojan Masanovic (MDPI AG, 2022)
The aim of this cross-sectional study was to determine the differences in the morphological characteristics and situational precision among younger and older groups of handball players. The sample of participants consisted of 30 handball players, members of the younger category of the Al-Ahli handball club (Bahrein), divided into two groups: older (U16, n = 18) and younger (U15, n = 12). To evaluate their morphological characteristics, eight variables were measured, while two standardized tests were used to evaluate their situational precision. The results indicate that a statistically significant difference between the groups was noticeable for nine variables in total, seven in morphology (body height, p = 0.010; body mass index, p = 0.049; arm length, p = 0.009; upper arm length, p = 0.016; lower arm length, p = 0.040; the planimetric parameter of the hand, p = 0.005; hand length p = 0.004) and two in situational precision (the standing shot, p = 0.003; the jump shot, p = 0.17), and that the achieved difference ranges from a medium to a large effect. For only one variable (body mass, p = 0.734), significant difference was not determined between the groups. It was also determined (by Cohen's criterion) that handball players with higher longitudinal dimensionality achieve better results for specific precision. Therefore, when selecting young handball players, the aforementioned dimensions should be taken into consideration as predictors of success.